Association between higher expression of interleukin-8 (IL-8) and haplotype −353A/−251A/+678T of IL-8 gene with preeclampsia: A case–control study. Issue 52 (December 2016) - Sun, Lei; Mao, Dongwei; Cai, Yan; Tan, Wenhua; Hao, Yanlan; Li, Lin; Liu, Wei
Abstract : Abstract: Preeclampsia (PE) is a common pregnancy-specific disorder associated with significant maternal and fetal morbidity and mortality worldwide. The present study was performed to investigate the role of a CXC chemokine interleukin-8 (IL-8), in the pathogenesis of PE. IL-8 expression levels were assessed in placental and serum samples from 160 pregnant women with PE (N = 68 severe, 92 mild) and 140 healthy donors. Results from enzyme-linked immunosorbent assay showed that the concentration of serum IL-8 in PE patients (180.27 ± 5.81 ng/L) was significantly higher than that in healthy controls (41.57 ± 5.67 ng/L). Patients with severe PE had even higher serum IL-8 levels. Similar messenger RNA and protein expression patterns of IL-8 in placental tissues were confirmed by quantitative real-time polymerase chain reaction and immunohistochemical assay (N = 30 each in the mild PE, severe PE, and control groups). In addition, single nucleotide polymorphisms of IL-8 gene were detected with polymerase chain reaction-restricted fragment length polymorphism/SSP. The frequency of IL-8 -251A allele was significantly higher than that in controls (58.4% vs 48.9%, P < 0.05). The occurrence frequency of haplotype −353A/−251A/+678T (AAT) in PE subjects was 27.2% as compared to 21.9% in the control participants ( P < 0.05). Our study reveals that IL-8 expression is positively associated with the severity of PE. Presence of haplotype AAT in pregnant women appears to be a risk factor for PE.